The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.3109/00365549509019005
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant Disseminated Toxoplasmosis in an HIV Patient

Abstract: Disseminated toxoplasmosis in AIDS is a rare condition. We present an unusual case of a fulminant form of disseminated toxoplasmosis in a young male homosexual. He was a 30-year-old HIV-positive (diagnosed 4 months earlier), admitted with a 5-day history of diarrhea, vomiting, fever, and cough. He had been generally healthy except for an 8-week history of weight loss and malaise. On admission, except for a temperature of 37.6 degrees C, the physical examination was normal. He was treated symptomatically. Four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…In both patients, clinical and laboratory findings were similar to findings for sepsis or septic shock, and death occurred quickly (6). Al-Kassab et al reported similar findings in an HIV patient with a normal clinical examination and normal chest x-ray at presentation but with acute respiratory distress and demise within 5 days (10). A similar patient with acute disseminated T. gondii infection with massive organ involvement during primary HIV infection was also described by Signorini et al (11).…”
Section: Discussionsupporting
confidence: 60%
“…In both patients, clinical and laboratory findings were similar to findings for sepsis or septic shock, and death occurred quickly (6). Al-Kassab et al reported similar findings in an HIV patient with a normal clinical examination and normal chest x-ray at presentation but with acute respiratory distress and demise within 5 days (10). A similar patient with acute disseminated T. gondii infection with massive organ involvement during primary HIV infection was also described by Signorini et al (11).…”
Section: Discussionsupporting
confidence: 60%
“…The occurrence of these conditions has been attributed to the transient but profound immune depression which is associated to acute HIV infection. Toxoplasmosis is a well recognized manifestation of AIDS, but the disseminated disease is a rare condition [1]. We describe a case of disseminated toxoplasmosis during primary HIV infection.…”
mentioning
confidence: 93%
“…Toxoplasmosis has been reported to cause myocarditis in man, but the majority of reports are limited to immunocompromised individuals (Al-Kassab et al 1995), typically following transplantation (Mayes et al 1995, Gallino et al 1996, Hermanns et al 2001. Similar reports are rare in the cat.…”
mentioning
confidence: 99%